Milk Supplementation as a Potential Intervention for Overcoming Anemia and Chronic Energy Deficiency during Pregnancy - Fikawati, Sandra; Syafiq, Ahmad (Jurnal Gizi dan Pangan, 2023)
This study aimed to determine the effect of milk supplementation on Mid-Upper Arm Circumference (MUAC) and hemoglobin level in pregnant women. It is a quasi-experimental study conducted from May to August 2019. The sampling was done by purposive sampling, and 108 pregnant women were recruited and divided into two groups: intervention group and non-intervention group. The intervention group received Fe-fortified milk supplementation, and the non-intervention group received education on anemia prevention. Data were analyzed using paired t-test. The result was that providing milk supplementation to pregnant women for three months could significantly increase MUAC and prevent further decline in hemoglobin levels.